Enuresis profile in 6-7 year-old children at five elementary schools in Sario district, Manado - Adrian Umboh; Astrid A. Malonda; T. A. Sudjono (Indonesian Pediatric Society Publishing House, 2016)
Background Enuresis is inappropriate urination by a child who has reached an age which bladder control is expected. The etiology is unknown, but some factors influence it. Objective To identify enuresis profiles in 6-7 year-old children. Methods It was a descriptive prospective study at five elementary schools in Sario district Manado from May to September 2005. Data were obtained by questionnaires. Results Out of 63 children with enuresis, 67% aged 6 years, 57% were male, 37% had enuresis more than 4 times a month, 64% had enuresis more than 8 times a day. No one had complaint of urinary tract infection. Most cases (70%) had enuresis since birth, 51% of cases got toilet training at the age of 3-4 years old. None of enuretic children had divorced parents. Nocturnal enuresis occurred in 81% of cases, 54% of cases had 4 family members, 30% of cases had family history of enuresis. Conclusions Enuresis in 6-7 year old children is most commonly seen in boys. Enuresis mostly happens for more than 4 times in a month with urination more than 8 times a day. There is no complaint of urinary tract infection. Most of the cases have enuresis during nighttime. Toilet training starts by the age 3-4 years old. Most cases had enuresis since birth. They came from a family with 4 family members, and in most situation no family history of enuresis is found.